2018
DOI: 10.1101/gr.233551.117
|View full text |Cite
|
Sign up to set email alerts
|

Hidden variation in polyploid wheat drives local adaptation

Abstract: Wheat has been domesticated into a large number of agricultural environments and has the ability to adapt to diverse environments. To understand this process, we survey genotype, repeat content, and DNA methylation across a bread wheat landrace collection representing global genetic diversity. We identify independent variation in methylation, genotype, and transposon copy number. We show that these, so far unexploited, sources of variation have had a significant impact on the wheat genome and that ancestral me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 49 publications
2
31
0
Order By: Relevance
“…Although the known population structure of the selected accessions in this study was recapitulated with methylation data, the level of methylation variation was linked to the overall genetic distance between any given samples. This result is similar to reports of natural Arabidopsis thaliana populations [6,12,25] and across a landrace Wheat collection [26]. Methods as described here, can dissect this confounding between genetics and epigenomics, to capture an additional piece of the missing heritability.…”
Section: Discussionsupporting
confidence: 87%
“…Although the known population structure of the selected accessions in this study was recapitulated with methylation data, the level of methylation variation was linked to the overall genetic distance between any given samples. This result is similar to reports of natural Arabidopsis thaliana populations [6,12,25] and across a landrace Wheat collection [26]. Methods as described here, can dissect this confounding between genetics and epigenomics, to capture an additional piece of the missing heritability.…”
Section: Discussionsupporting
confidence: 87%
“…In the last decades, exotic parents have been used in breeding programmes with the aim of introducing greater diversity into elite gene pools (Singh et al, 2018). The exotic parents that are most frequently used are those from the primary gene pool represented by germplasm that share a common genome but that have become isolated from mainstream gene pools such as landraces (Reynolds et al, 2009a,b), which have been shown to be not only genetically, but epigenetically diverse (Gardiner et al, 2018). The secondary gene pool that has also been used is represented by closely related genomes that can be utilised through inter-specific hybridisation, and would include the development of so-called 'synthetic' or 're-synthesised' wheat, where a tetraploid durum wheat has been hybridised with Aegilops tauschii, the ancestral donor of the D genome, to recreate hexaploid bread wheat (Mujeeb-Kazi et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The recent study of these decoy F-box protein networks involved in circadian clock function strongly endorses the importance of such truncated F-Box microProteins in the regulation of plant development in response to environmental stimuli (Lee et al 2018). Equally, the inferred regulation of protein function and gene expression by methylation and other similar transient modifications are known to regulate development and stress adaptation in crops (Gardiner et al 2018;Wang et al 2011).…”
Section: Discussionmentioning
confidence: 96%